1379Has the reporting quality of published randomised controlled trial protocols improved since the SPIRIT statement?. (2nd September 2021) - Tan, Aidan; Tan, Zet; Li, Tom; Harris, Ian; Naylor, Justine; Siebelt, Michiel; Tiel, Jasper van; Pinheiro, Marina; Harris, Laura; Chamberlain, Kira; Adie, Sam
Abstract: Background: The impact of the SPIRIT statement on the reporting quality of RCT protocols in health research is unknown. This methodological study aimed to determine the reporting quality of published randomised controlled trial (RCT) protocols before and after the SPIRIT statement, and any association with author, trial or journal factors. Methods: RCT protocols were identified by searching MEDLINE, Embase and CENTRAL, included if published in full-text, English language and a peer-reviewed journal, and assessed with the SPIRIT statement checklist items. Results: 300 RCT protocols were retrieved; 150 from the period immediately before the SPIRIT statement and 150 from a recent period after the SPIRIT statement. 47.9% (95% CI, 46.5% to 49.3%) of checklist items were adequately reported in RCT protocols before the SPIRIT statement and 56.7% (95% CI, 54.9% to 58.5%) after the SPIRIT statement. This represents an 8.8% (95% CI, 6.6% to 11.1%; p < 0.0001) mean improvement in the overall proportion of checklist items adequately reported since the SPIRIT statement. The factors associated with higher reporting quality of RCT protocols in multiple regression analysis were author expertise or experience in epidemiology or statistics, multicentre trials, longer protocol word length and publicly reported journal policy of compliance with the SPIRIT statement. Conclusions: The overall reporting quality of RCT protocols has significantly improved since the SPIRIT statement, although a substantial proportion of individual checklist items remain poorly reported. Key messages: Continued, concerted and coordinated efforts are required by journals, editors, reviewers and investigators to improve the completeness and transparency of RCT protocols.